2020
DOI: 10.4149/bll_2020_067
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Slovak version of the Wijma Delivery Expectancy/Experience Questionnaire (W-DEQ), version A

Abstract: AIM: This study aimed to assess the psychometric characteristics of the Slovak translation of the version A of Wijma Delivery Expectancy/Experience Questionnaire (SW-DEQ) among healthy Slovak pregnant women. METHOD: Exploratory factor analysis (EFA) of the SW-DEQ was performed. Several coeffi cients of internal consistency were employed for the whole scale as well as for separate factors. Concurrent/convergent validity was assessed by correlation analysis of the overall SW-DEQ score with State-Trait Anxiety In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…However, according to Kottner et al (2011), for an instrument to be able to be used to take clinical decisions, the minimum Cronbach's alpha acceptable should be 0.90 [79]. Furthermore, these values are very similar to those obtained in other studies in which the reliability was measured with the Cronbach's alpha coefficient [13,34,42,45,47,49]. Additionally in this study the homogeneity coefficient was calculated for the corrected items estimating the correlations of each item with the total scale and with its corresponding subscale.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, according to Kottner et al (2011), for an instrument to be able to be used to take clinical decisions, the minimum Cronbach's alpha acceptable should be 0.90 [79]. Furthermore, these values are very similar to those obtained in other studies in which the reliability was measured with the Cronbach's alpha coefficient [13,34,42,45,47,49]. Additionally in this study the homogeneity coefficient was calculated for the corrected items estimating the correlations of each item with the total scale and with its corresponding subscale.…”
Section: Discussionsupporting
confidence: 74%
“…The explained variance of the structure with four dimensions was 55%. This variance was very similar to that found in the majority of studies that have validated this questionnaire [13,33,34,37,[41][42][43][44]47] and was only less than that found in the study carried out by Abedi et all., Moghaddam Hosseim et al y Pitel et al [45,46,49]. Although the percentage of explained variance found in this study could be considered to be low, it is not currently recommended to use the interpretation of explained variance as the only indicator of factors identified.…”
Section: Discussionmentioning
confidence: 74%
“…The reliability (Cronbach alpha) of the WDE-Q questionnaire in the present study was 0.88. The Slovak version of the WDE-Q was validated by Pitel et al (2020) and has shown good psychometric properties. A pilot study involving five respondents was conducted to evaluate the quality of the questionnaires.…”
Section: Measuring Instrumentsmentioning
confidence: 99%
“…We thought different dimensions may be due to cultural differences or insufficient data. Moreover, the items of the factor “Concern for the child” was consistent with the Slovak version [ 45 ]. In addition, based on the standard of model fitting indices, χ 2 /df was 2.96 less than 3.0, RMSEA was 0.104 approximate to 0.1, and IFI, TLI, and CFI were greater than 0.7.…”
Section: Discussionmentioning
confidence: 67%